A new species of Platanthera (Orchidaceae, Orchideae, Orchidinae) from Michoacán, Mexico - Espejo Serna, Adolfo; Lopez-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 1994)
Platanthera calderoniae López-Ferrari & Espejo, a riparian species from San Miguel del Monte, Municipio of Morelia in the State of Michoacan, Mexico is described as new to science.